Narrativas acerca da sujeição criminal de egressos da Fundação de Atendimento Socioeducativo (FUNASE) - Silva, Elãine dos Santos Dias da (2022)
This research takes base through the observation of the impacts from the experience of admissions and participation in the New Opportunities Project (a policy attention to young people in the process of resocialization) in their trajectory after leaving the detention center FUNASE. The empirical proposal is substantially made up of in-depth interviews with young people from the socio-educational system of Pernambuco who have been subjected to the socio-educational measure of restriction of freedom and who have been assisted by the policy of care for former socio-educated students. We sought here to analyse the narratives of the research subjects, regarding to their experiences, through the concepts of criminal subjection (Misse), stigma (Goffman) and the theory of deviance (Becker). Preliminary conclusions have shown that the symbolic instruments mobilized by the egresses in their narratives reveal experiences that are crossed by the process of criminal subjection, before and after admission, in addition to attempts to detach labels and manipulate stigmas, ranging from changes in of speaking and behaving to the ties of christian churches and strategic choices of omission of past experiences, which permeate the construction of their subjectivities, their trajectories and their future projections.